2020
DOI: 10.46303/jcve.03.01.3
|View full text |Cite
|
Sign up to set email alerts
|

Implementing non-traditional assessment strategies in teacher preparation: Opportunities and challenges

Abstract: Assessment and grading in higher education have traditionally focused on “A” through “F”, or point-based alpha-numeric letter grades and subjective, independent grading systems. Despite the ubiquity of this system, there are no universal guidelines on how to assess student learning on that scale. What can be problematic about “the way things have always been” is that students are frequently de-humanized; higher education faculty often focus on compliance and authoritarian teaching rather than engaging in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Studies have demonstrated how hip-hop pedagogies have benefitted student experiences and academic outcomes (Dimitriadis, 2009;Hill, 2009;Morrell & Duncan-Andrade, 2002;Parker, 2020). Due to the pioneering efforts of levying battle rap as an academic tool, educators must critically evaluate intended and unintended implications since new and nontraditional learning opportunities often engenders new obstacles (Newton, et al, 2020;Petchaur, 2011). Nevertheless, cultivation of students' critical consciousness continues to be warranted given our sociopolitical times.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated how hip-hop pedagogies have benefitted student experiences and academic outcomes (Dimitriadis, 2009;Hill, 2009;Morrell & Duncan-Andrade, 2002;Parker, 2020). Due to the pioneering efforts of levying battle rap as an academic tool, educators must critically evaluate intended and unintended implications since new and nontraditional learning opportunities often engenders new obstacles (Newton, et al, 2020;Petchaur, 2011). Nevertheless, cultivation of students' critical consciousness continues to be warranted given our sociopolitical times.…”
Section: Discussionmentioning
confidence: 99%
“…Both ideals of the ungrading practice were important to me, in particular alleviating the stress and anxiety that interns express as they span the boundary between college student and teacher. PDSP 19,1 Newton et al (2020) identify approaches to ungrading that include a goal approach, a conferencing approach, and a reflection approach. In working with the PDS interns, I focused on the conferencing and reflection approaches and incorporated both during the semester.…”
Section: Ungradingmentioning
confidence: 99%
“…While I do not suggest that the interns enter their clinical placement and first job as a teacher and attempt to disrupt the evaluation and grading practices, I do want them to approach it thoughtfully. Implementing an ungrading practice that included self-assessment opportunities, individual conferences and formative assessment activities throughout the semester would model the evaluation process that they would experience as teachers (Newton, Williams & Feeney, 2020) and perhaps encourage them to implement such practices in their own classroom.…”
Section: Ungradingmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers Newton, Williams and Feeney (2020) argued that in traditional assessment, without using rubrics, teachers give grades to students like A, B or C, which do not make better sense to the students on which basis they got these grades. These types of practices create questions in the minds of all the stakeholders (e.g., student-teachers and others etc.)…”
Section: Introductionmentioning
confidence: 99%